THE EFFECT OF ECONOMIC VALUE ADDED (EVA) ON PRICE TO BOOK VALUE THE ROLE OF INSTITUTIONAL OWNERSHIP IN RETAIL SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Apriyani, Apriyani; Aisyah F Pulungan, Nur (Dinasti International Journal of Economics, Finance & Accounting, 2020)
This study examines and analyzes the effect of Economics Value Added (EVA) on the price to book value mediated by institutional ownership in retail sector companies listed on the Indonesia Stock Exchange (IDX). The object of this study is the sector of retail with shares of sharia when listed on the Indonesia Stock Exchange (BEI) period 2015-2019. In order to achieve the goals and objectives, the company increases it’s value by increasing shareholders. Improving the walfare on shareholders can be done through investment and financial policies, and is reflected in share price in the capital market. The higher the share price, the better the owner’s walfare, and the company’s value will also increase. The population of this research is the retail companies as many as 27 companies when the sample is 12 company’s by using a purposive sampling method met criteria for the sample. The data is further analyzed using SmartPLS Vs.3.2.9 by looking at the result of descriptive analysis, coefficient path, and path analysis. The result of the study showed that Economic Value Added (EVA) has a negative and significant effect to Price to Book Value (PBV), the Economic Value Added (EVA) has a negative and not significant effect to institutional ownership, the institutional ownership has a negative and significant effect to Price to Book Value (PBV), in addition institutional ownership does not mediate the relationship between Economic Value Added (EVA) and Price to Book Value (PBV).